Gross and microanatomical studies on the moderator bands (septomarginal trabecula) in the heart of mature Dromedary camel (Camelus dromedarius) - Ghonimi, Wael; Abuel-Atta, Ahmad Awad; Bareedy, Mohamed Hafez; Balah, Ahmad (Journal of Advanced Veterinary and Animal Research, 2014)
The current work was carried out to investigate the gross and microanatomical features of moderator bands (septomarginal trabecula) in camel heart. Ten hearts were collected from healthy mature dromedary camels. Anatomically, the moderator bands were present in both right and left ventricles. In right ventricle, the walls had one muscular moderator band which was extended from the interventricular septum to the opposite ventricular wall especially to the papillary muscle. In left ventricle, there were two bands; one extended from the interventricular septum to the papillary muscles, and the other one was present in various places especially in the apex running as a thin thread-like band across the left ventricular wall. Histological examination revealed that the moderator band consisted of two major layers; the central (core) myocardium and the peripheral endocardium, acting as band capsule. The myocardium had two bundles; the contractile cardiac muscle bundles and the Purkinje fiber bundles. The endocardium consisted of three layers; the endothelial layer of simple squamous epithelium, the subendothelial layer of loose connective tissue and the subendocardial layer, connecting the endocardium with the myocardium. DOI: http://dx.doi.org/10.5455/javar.v1i2p24-31 J. Adv. Vet. Anim. Res., 1(2): 24-31, June 2014